The forked flap repair for hypospadias - Anil Chadha; Amitabh Singh (Indian Journal of Plastic Surgery)
Context: Despite the abundance of techniques for the repair of Hypospadias, its problems still persist and a satisfactory design to correct the penile curvature with the formation of neourethra from the native urethral tissue or genital or extragenital tissues, with minimal postoperative complications has yet to evolve. Aim: Persisting with such an endeavor, a new technique for the repair of distal and midpenile hypospadias is described. Materials and Methods: The study has been done in 70 cases over the past 11 years. The "Forked-Flap" repair is a single stage method for the repair of such Hypospadias with chordee. It takes advantage of the rich vascular communication at the corona and capitalizes on the established reliability of the meatal based flip-flap. The repair achieves straightening of the curvature of the penis by complete excision of chordee tissue from the ventral surface of the penis beneath the urethral plate. The urethra is reconstructed using the native plate with forked flap extensions and genital tissue relying on the concept of meatal based flaps. Water proofing by dartos tissue and reinforcement by Nesbit′s prepucial tissue transfer completes the one stage procedure. Statistical Analysis: An analysis of 70 cases of this single stage technique of repair of penile hypospadias with chordee, operated at 3 to 5 years of age over the past 11 years is presented. Results and Conclusion: The Forked Flap gives comparable and replicable results; except for a urethrocutaneous fistula rate of 4% no other complications were observed.